ANALISIS PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE UNTUK MENINGKATKAN PARTISIPASI BELAJAR PADA MATA PELAJARAN IPAS SEKOLAH DASAR. - Fajriah, Febi; Kornia Sari, Desi; Ayuni Esya Putri, Febby; Sofwan, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Think Pair Share (TPS) learning model in improving students’ learning participation in Science and Social Studies (IPAS) subjects at the elementary school level. Low student participation in IPAS learning activities is a common problem encountered in the field, characterized by minimal active involvement of students in discussions, question-and-answer sessions, and problem-solving activities. This study employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The subjects of the study were the teacher and fourth-grade students of SDN 182/1 Hutan Lindung, Jambi City. The results showed that the implementation of the TPS model significantly increased students’ active participation, including asking questions, answering questions, engaging in discussions, and expressing opinions. The TPS model proved effective in creating a more interactive, collaborative, and student-centered learning environment. The implications of this study provide recommendations for educators to integrate the TPS model as an innovative learning strategy in IPAS instruction at the elementary school level.